Measuring landscapes – A storytelling rhythm through shared places and itineraries - Adriana Ghersi; Silvia Pericu; Federica Delprino; Stefano Melli (Agathón)
The experimentation in three different territories makes it possible to develop a modular narrative based on specific landscapes through itineraries and remarkable points capable of representing their peculiarities. Understanding the quality of the different landscapes as the expression of local values and cultures, involving the communities for a shared narration of the memory and the most significant places and promoting them, and rediscovering the potential of experiential tourism are the objectives of the research. It envisages an integrated approach to the theme of knowledge and enjoyment of the landscape, identifying specific rhythms in the places to cross, through innovative digital tools and sharing with the local communities, looking for solidarity and activation of relations between users and inhabitants, for a dynamic storytelling that allows for further enrichment.